The Persuasive Communication Strategies of Mediators in Divorce Case Mediation at the Teluk Kuantan Religious Court - Teddy Niswansyah; Muhammad Firdaus; Anuar Rasyid (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study examines the persuasive communication strategies employed by mediators in divorce case mediation at the Teluk Kuantan Religious Court. Using a qualitative research approach, the study seeks to understand how mediators design and implement communication strategies to manage marital conflict and encourage constructive dialogue between disputing spouses. Data were collected through in-depth interviews, observation of mediation sessions, and document analysis, with the researcher serving as the primary research instrument. The findings reveal that mediators apply a series of structured strategies across the stages of planning, implementation, and evaluation, including conflict analysis, persuasive message formulation, empathetic communication, language reframing, emotional approaches, and caucus meetings. The effectiveness of these strategies is influenced by supporting factors such as mediator competence, institutional mediation procedures, and a conducive mediation environment, as well as inhibiting factors including emotional intensity, predetermined decisions to divorce, communication breakdowns, power imbalances, time constraints, and external social pressures. Overall, the study highlights that persuasive communication is central to the mediation process; however, its success depends not only on mediator skills but also on the psychological readiness of the parties and the broader institutional context of court-based mediation